Structural features of arterial grafts important for surgical myocardial revascularization: Part II – Histology of the radial, inferior epigastric, and right gastroepiploic arteries - Labudović Borović, Milica; Kostić, Jelena T; Borović, Saša D; Zaletel, Ivan V; Dželebdžić, Sanja M; Puškaš, Nela S; Kostić, Jelena V; Trifunović, Zoran Ž (Vojnosanitetski pregled, 2016)
Key words:           coronary artery bypass; vascular patency; histology; radial artery; epigastric arteries; gastroepiploic artery.
Keywords: arterial grafts; surgical myocardial revascularization; radial artery; inferior epigastric artery; right gastroepiploic artery; CABG; Arteries